What Did You Do Today? Variability in Daily Activities is Related to Variability in Daily Cognitive Performance. (12th December 2017) - Bielak, Allison A M; Mogle, Jacqueline; Sliwinski, Martin J
Abstract: Objectives: Are the activities we do each day related to fluctuations in our daily cognitive performance? Positive longitudinal associations between cognitive, physical, and social activities and cognitive ability in adulthood are well established. However little is known about how this relationship may operate at the daily level. Methods: Community-dwelling participants 60–90 years of age ( M = 69.41; n = 146) reported their activity participation and completed cognitive tests online for 7 consecutive days. Results: Multilevel models showed that daily activities covaried with daily cognitive performance, indicating fluctuations in the activities that a person engaged in across the week were associated with corresponding changes in their daily speed, memory, and reasoning. This was strongest for social activities where on days when individuals engaged in more routine activities with social-private characteristics than usual, they had higher memory scores and responded faster. Discussion: This information could be particularly relevant to the daily lives of older adults, especially those experiencing cognitive decline.